ANALISIS ISI FOTO BERITA PADA RUBRIK â€œJEPRETâ€ DI HARIAN POS METRO MEDAN - Taufik Walhidayat Novri Maulana (Universitas Medan Area, 2013)
The research aims is to observe content of photo news on â€œJepretâ€ rubric of Pos Metro daily. A photo has the ability to present a news in detail. Reader does not explanation such narrative description. Therefore, a photo able to record anything and objectively present the event that contain element of news. This research use content analysis to observe and measure the content of communication medium. The result shows that the appearance and size of â€œJepretâ€ rubric on the daily accordingly to Pos Metro policy,